(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Neonatal hyperbilirubinemia is one of the most common clinical conditions observed in the early neonatal period and remains a significant cause of preventable neurological morbidity worldwide. Although the majority of newborns develop physiological jaundice, a considerable proportion are at risk of progressing to severe hyperbilirubinemia with potential complications such as acute bilirubin encephalopathy and kernicterus. Advances in understanding bilirubin metabolism, neurotoxicity mechanisms, and risk factors have led to the development of modern diagnostic and management strategies